Chemical Analysis of Chicken Sempol for Food Safety Program in Karanganyar Regency: chicken sempol ,chemical analysis, karanganyar regency, chemical characteristics, chemical composition - Wijayanti, Desna Ayu (Universitas Veteran Bangun Nusantara, 2023)
This aims study to evaluate chemical composition of chicken sempol in Karanganyar Regency. The sampling location of the research was carried out at sempol A sellers (Karanganyar Square area), sempol B (Pujasera Streetfood area), sempol C (Jl. Lawu area). The research method used a Complete Randomized Design (RAL) with 3 treatments and 4 repeats. Sampling was carried out by nonprobability sampling and research method with descriptive quantitative analysis. Data analysis in this study used Analysis of Variance (ANOVA). The findings demonstrate significant (P<0.05) variations in protein content, water content, carbohydrate content, fat content and boraks and formalin analysis the chicken sempol. The highest chemical content of sempol is carbohydrate which is 51,12% in sempol A. The highest water content in sempol A (48.73%), the highest protein content in sempol C (10.76%), carbohydrate content A (51.12%), the highest fat content in sempol B (11.87%). Chemical quality tests reveal protein content at 9.59%, water content at 47.77%, carbohydrate content at 47.17%, fat content at 9.21%, the result and discussion of boraks and formalin on sempols is negative (-). Sempol ayam at traders in Karanganyar has different chemical characteristics. This study concludes that chicken sempol with chemical quality can provide information on the quality of food or processed products that are good for consumers so as to increase the nutritional value of food products. Keywords : chicken sempol ,chemical analysis, karanganyar regency, chemical characteristics, chemical composition